An exploratory study of the influence of video viewing on preservice teachers' teaching activity: normative versus developmental approaches - Cyrille Gaudin; Simon Flandin; Luc Ria; Sébastien Chaliès (Firenze University Press, 2014)
Very little empirical evidence is available concerning the influence of video viewing on preservice teachers' teaching activity. This article presents an exploratory study putting into perspective the influence of two video-based vocational education programs on pre-service teachers' teaching activity. These innovative programs have been designed on the same conceptual framework - an activity-based framework for work analysis (Durand, 2013) - but using two different theoretical and instructional approaches: the "normative" one (Berducci, 2004; Nelson, 2008) and the "developmental" one (Varela, 1989). With both approaches, the results highlighted that video viewing influence pre-service teachers' teaching activity, provided that: (i) preservice teachers' professional concerns "resonate" with what they are viewing, and (ii) preservice teachers adopt, adapt or invent a new way to act from what they viewed. Supported by self-confrontation interviews data, benefits and limitations of each approach are presented and discussed.   Sono disponibili scarse evidenze circa l'influenza della visualizzazione di video sull'attività didattica di insegnanti in prima formazione. Questo articolo presenta uno studio esplorativo sull'impatto di due programmi progettati sulla base del medesimo quadro concettuale - un activity-based framework di analisi del lavoro (Durand, 2013) - ma con due diversi approcci teorici e didattici: quello "normativo" (Berducci, 2004; Nelson, 2008) e quello di "sviluppo" (Varela, 1989). In entrambi i casi i risultati evidenziano che la visualizzazione di video influenza l'attività didattica degli insegnanti in formazione, a condizione che: (i) gli interessi professionali degli insegnanti in formazione siano legati a ciò che essi visualizzano, e (ii) gli insegnanti in formazione adottino, adattino o inventino un nuovo modo di agire a partire da quello che hanno visto. Supportati da dati estrapolati da interviste di auto-confronto, sono presentati e discussi i vantaggi e i limiti di ciascun approccio.